Validation of cone beam CT scan for measurement of palatal depth in study casts - Radzi, Z.; Yahya, N. A.; Abu Kasim, N. H.; Abu Osman, N. A.; Yusof, Z. Y. M.; Mohd, F. N.; Noor, N. H. M.; Jamaludin, M.; Othman, S. A.; Obaidellah, U. H.; Mohamed, N. H.; Kadir, R.; et al. (SPRINGER, 233 SPRING STREET, NEW YORK, NY 10013, UNITED STATES, 2008)
The purpose of this study was to validate the use of digital dental study casts obtained from Cone beam CT Scan (CBCT) against gold standard; that is traditional dental study cast measured with digital caliper.